Sustainability in Brazilian Citriculture: Three Decades of Successful Biological Control of Insect Pests - Parra, José Roberto Postali; Garcia, Adriano Gomes; Diniz, Alexandre José Ferreira; Bento, José Maurício Simões (Frontiers in Agronomy, 2022)
Citrus insect pests has grown worldwide, concerning entomologists and farmers especially because of the high demand for food that makes it to our tables. The use of pesticides brought several issues, such as the negative impacts on the human health, pollution, and insect resistance. In this context, more environmentally-friendly strategies have been demanded by governments and consumers. In this review, we present three remarkable examples of pest management in Brazil that involved many researchers from different expertise areas to develop more sustainable strategies to reduce the damages to citrus production. The case studies consisted of high-quality research funded by the Brazilian government and private institutions. In the first case, we report on the monitoring of the citrus fruit borer with sex pheromones, which significantly improved the control of this insect pest. Based on behavioral studies, it was recommended that delta traps containing pheromone attractant be installed on the upper third part of the plant. A recent study indicates the promising use of the egg parasitoid Trichogramma atopovirilia for biological control. In the second case, the biocontrol of the leafminer using Ageniaspis citricola is discussed. The insect pest was introduced into Brazil in 1996, causing losses of up to 60 kg of fruit per tree. The solution for this problem was the introduction of the parasitoid Ageniaspis citricola, originally from Asia. The pest was successfully controlled by the parasitoid, which was able to adapt to different citrus-producing regions in Brazil. Finally, the most emblematic successful case in Brazil is the biological control of the Asian citrus psyllid (ACP), Diaphorina citri, using Tamarixia radiata. ACP is the most important citrus pest because it causes indirect damage by transmitting the gram-negative bacteria that cause HLB (huanglongbing) in citrus areas. HLB is a vicious disease that has no cure: after being infected, the plants present chlorosis of the leaves, production of yellow shoots, and die within 2–3 years. The combination of laboratory tests, insect monitoring and computational modeling showed the efficacy of T. radiata against D. citri, which reduces the number of infected trees.